Model Pengembangan UMKM dengan Pendekatan KBK (Kluster Bordir Dan Konveksi) di Desa Padurenan Kudus - Martini, Tina; Suhadi, Suhadi; Sodik, Amirus (Universitas Islam Negeri Sunan Kudus, 2019)
This study aims to determine the development model of small and medium enterprises with the KBK approach (Embroidery and Convection Cluster) in Padurenan Village, Kudus Regency. The contribution of research is expected to add to the contribution of thought and knowledge in business management, especially relating to the model of developing small and medium enterprises with the KBK approach (Embroidery and Convection Clusters) in Padurenan Village, Kudus Regency. The context of this research is business development with the KBK approach to Content UKM in Padurenan Village. The research approach used in this study is a qualitative research method. The location of the study was carried out on SME players who were members of the KBK in Padurenan Village, Kudus Regency. Technique of collecting data by interview, observation, documentation. The results showed that UKM in Padurenan Village from the side of facilitation, training, comparative studies they often received, and the outputs that they could increase the skills of employees, the maturity of managerial companies, as well as communication or relations with outside parties increasingly well established. Under the command of KSU Padurenan Jaya, communication between SMEs is established and the means of information are often one of them in participating in activities that are developing their business. Researchers also found conditions where they were still not optimal in terms of financial statements. They have participated in training in financial report preparation for SMEs as well as business planning but the reality in the field of the recording system does not meet the existing standards. As a result of recording that does not meet these standards, the company's personal wealth has not been separated. This is disturbing in the company's report progress assessment.